STUDIES ON THE DIVERSITY OF PREDATORY COCCINELLID BEETLES (COLEOPTERA) IN DIFFERENT AGRO-CLIMATIC ZONES OF HIMACHAL PRADESH - P. L. SHARMA,; USHA CHAUHAN,; K. C. SHARMA, (The Bioscan, 2015)
All the four agro-climatic zones of Himachal Pradesh varying from sub-tropical to dry- temperate conditions were surveyed for the diversity of predatory coccinellids from March 2011 to November 2013. In total 36 species of predatory coccinedlids belonging to 24 genera, 11 tribes and 4 sub-families were recorded from different agro- climatic zones. Among these, 18 species viz. Brumoides suturalis (Fabricius), Chilocorus nigrita (Fabricius), Rodolia octoguttata Weise, Sumnius vestita (Mulsant), Coccinella luteopicta (Mulsant), Coelophora bissellata Mulsant, Coelophora saucia (Mulsant), Phrynocaria perrotteti (Mulsant), Propylea dissecta (Mulsant), Psyllobora bisoctonotata (Mulsant), Cryptogonus orbiculus Gyllenhall, Cryptogonus trioblitus (Gorham), Ortalia vietnamica Hoang, Ortalia sp., Scymnus nubilus Mulsant. Stethorus sp., Pharoscymnus flexibilis Mulsant and Pharoscymnus horni Weise were reported for the first time from the state. Species richness varied with agro-climatic conditions and was highest (22 species each) under sub-tropical and sub-temperate climate followed by 10 and 7 species under wet temperate and dry temperate conditions. Coccinella sptempunctata, Hippodamia varigieta and Cheilomenes sexmaculata occupied all the 4 agro-climatic zones, however, Chilocorus infernalis, Harmonia eucharis, Propylea luteopustulata and Priscibrumus uropygialis were confined to temperate climate. Since predatory coccinellids were active throughout the state against different pests, there is a need to conserve them by developing bio-intensive IPM strategies.